The putative role of insulin-like growth factor (IGF)-binding protein 5 independent of IGF in the maintenance of pulpal homeostasis in mice - Saito, Kotaro (Regen Ther, 2019)
Although insulin-like growth factor binding protein 5 (IGFBP5) may play a crucial role in activating the functions of periodontal and bone marrow stem cells, the factors responsible for regulating the maintenance of dental pulp stem cells (DPSCs) remain to be clarified. This study aimed to elucidate the role of IGFBP5 in maintaining pulpal homeostasis during tooth development and pulpal healing after tooth injury in doxycycline-inducible TetOP-histone 2B (H2B)-green fluorescent protein (GFP) transgenic mice (GFP expression was induced at E14.5 or E15.5) by using TUNEL assay, RT-PCR, in situ hybridization for Igfbp5, and immunohistochemistry for IGFBP5, Nestin, and GFP. To observe the pulpal response to exogenous stimuli, the roots of the maxillary first molars were resected, and the coronal portion was autografted into the sublingual region. Intense IGFBP5/Igfbp5 expression was observed in cells from the center of the pulp tissue and the subodontoblastic layer in developing teeth during postnatal Week 4. Intense H2B-GFP-expressing label-retaining cells (LRCs) were localized in the subodontoblastic layer in addition to the center of the pulp tissue, suggesting that slowly dividing cell populations reside in these areas. During postoperative days 3–7, the LRCs were maintained in the dental pulp, showed an IGFBP5-positve reaction in their nuclei, and lacked a TUNEL-positive reaction. In situ hybridization and RT-PCR analyses confirmed the expression of Igfbp5 in the dental pulp. These findings suggest that IGFBP5 play a pivotal role in regulating the survival and apoptosis of DPSCs during both tooth development and pulpal healing following tooth injury.